APLIKASI PEMBELAJARAN MATEMATIK BERBASIS MULTIMEDIA (Information Technology and Telematics, 2013)
Abstract - In the world of computer technology education can be used as a tool for supporting the learning program to solve a problem in the delivery of learning materials. The computer is quite effective and efficient way to explain something, because it can be presented through the images or sound. Making learning aid program aims to facilitate the students in learning mathematics class II. so that the resulting program is usually aids can help the role of teachers and parents to provide direction to the child in improving the learning process. Methods of data collection are include documentation and literature. The method selected was the development of methods development SDLC (System Development Life Cycle). That's because the SDLC steps in accordance with the method of system development. This discussion include: Learning materials, about the evaluation process, the evaluation report problems, and learning through vidieo.dengan exercises to test the extent to which students can understand the material provided by the learning assistance program.   Keywords: Mathematics, Learning, Multimedia